Mass Rallies: An Overview of Santri Rejection on the Five-day School Policy in Indonesia - Alnizar, Fariz (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2019)
The Regulation of Ministry of Education and Culture No. 23 of 2017 concerning School Day resulted in a tremendous wave of protest. The public takes part in different sides, the pro and the contra. This research uses a hermeneutical paradigm with causal historical analysis. The results of the study show that the refusal among the pesantren community is based on a robust doctrine of the fiqh rules as a form of orthodoxy and adherence to the values taught by the pesantren. Second, the government is playing with language on its policy. In the context of full-day school regulation, the government still uses euphemism as a strategy of education political ethic. Third, Nahdlatul Ulama (NU) has a very central role in rejecting the five-day school policy.